Essays on behaviour under risk - Sousa, Sergio Almeida de (2010)
This thesis consists of three essays on behaviour under risk. First, I investigate experimentally three related questions: (1) the effects of small-scale changes in wealth on risk attitudes; (2) whether potential changes in risk attitudes induced by such wealth increment are affected by (a) by the span of time this small-scale change in wealth has been anticipated for, and (b) the form taken by the wealth increment. There are three major results. One, whether risk attitudes are affected by a small-scale change in wealth depends on the form taken by the wealth increment. Two, that failure in replicating "house" money effect suggests that people may treat windfall money differently from earned money. Three, that the attitudes to risk are stable over the span of time we investigate. Second, I investigate how cognitive ability relates to consistency of behaviour under risk. Individual behaviour can be consistent in several forms. I find that individuals with higher cognitive ability display more consistent behaviour - in terms of choice and displayed type of risk preferences. Yet, in contrast to some recent studies, I find that individual measures of attitudes toward risk are not associated with cognitive ability. Third, I investigate the efficacy of a punishment mechanism in promoting cooperative behaviour in a public goods game when enforcement of punishment is uncertain. Numerous experimental studies have found that a sanctioning system can promote cooperative behaviour. But they rely on perfect enforcement of punishment. I find that a sanctioning system can no longer promote cooperative behaviour in a public goods game when punishment enforcement is a low-probability event.